PENGARUH KUALITAS PELAYANAN FRONTLINER TERHADAP KEPUASAN NASABAH PADA BANK BNI SYARIAH KCP KARTINI -DEPOK - ., Muhlis; ., Haryani (Economicus, 2019)
The purpose of this study was to determine how much the physical service variable, reliability, responsiveness, assurance and empathy affect customer satisfaction at BNI Syariah KCP Kartini. This study uses a questionnaire as an instrument to take a sample of 100 respondents, who are BNI Syariah KCP Kartini Depok customers. The results of data analysis using multiple linear regression showed that partially, just empathy had a positive and significant effect on customer satisfaction at BNI Syariah KCP Kartini. Simultaneously note that F statistic > F table so that Ho is rejected, meaning that together physical evidance, reliability, responsiveness, assurance and empathy affect satisfaction customer. The independent variable can explain the dependent variable that is customer satisfaction by 39.6% and the remaining 60.4 is explained by other variables not included in this analysis.